ANÁLISIS CLADÍSTICO DE S1MULIUM (PTERNASPATHA) ENDERLEIN CON DATOS SOBRE SU DISTRIBUCIÓN GEOGRÁFICA (DIPTERA: SIMULIIDAE) (Acta Entomológica Chilena, 2022)
Simulium (Pternaspatha) is a peculiar Southern South American blackfly subgenus, with 26 speciesdistributed along the Andes from Tierra del Fuego to SW Perú, and one species in Ecuador, It is amonophyletic taxon defined by two synapomorphies: 1) “female scutum gray, with 1 + I sublateral andmedian black, dusted, longitudinal stripes, median stripe divided longitudinally by a fine grayish line andabdomen with 1 + 1 whitish submedian spots with variable size and distribution among tergites”, and 2)“distimere of male genitalia subquadrate with slow concavity distally and subapical spine”, and withoutresemblance with the remaining tropical Sim ulium subgenera. A cladistic analysis was conducted using 24morphological characters from the male, female, pupa, and larva. Polarity of characteres was based on theoutgroup comparison method, using “blancasi” group, from Chile and the Peruvian desert. With mh* optionof Hennig86 program 12 most parsimonious cladograms were obtained, each with 44 steps and a consistencyÍndex of 0,97 and retention inder of 0,98; with bb* option 86 most parsimonious trees were obtained. A strictconsensus tree was calculated. This cladogram define two monophyletic groups that corresponded to“nemorale” and “nigristrigatum” groups in accordance to Coscaron and Wygodzinsky (1972). Two mapswith 5. (Pternaspatha) geographical distribution and relationships of ciados with biogeographical areas areadded.